Validated HPLC Method for the simultaneous determination of acyclovir and co‐administered vitamin B3 and gabapentin in spiked human plasma. Issue 7 (20th July 2018) - Sayed, Rania; El‐Masry, Manal; Hassan, Wafaa; El‐Mammli, Magda; Shalaby, Abdalla; Aboul‐Enein, Hassan Y.
Abstract: In this work, a new, sensitive and accurate high‐performance liquid chromatographic method for the simultaneous determination of acyclovir and co‐administered vitamin B3 and gabapentin used in treatment of herpes zoster disease was developed and validated. Protein precipitation with methanol was performed to extract the cited drugs from plasma. Thermo Hypersil (250 mm × 4.6 mm I.D, 5 μm particle size) column was used for the chromatographic separation. Isocratic elution of mobile phase consisting of methanol and 0.03 M potassium dihydrogen orthophosphate adjusted to pH 3.5 with 0.1% orthophosphoric acid (30:70, v/v) was used for separation. Photodiode array detector was used and detection was performed at 210 nm. The method was linear over the concentration range 1–100 μg/mL for both acyclovir and vitamin B3 and 5–150 μg/mL for gabapentin. The proposed method was validated and successfully applied for the commercial dosage forms of the three drugs and in human plasma. Statistical analysis of the results revealed its high accuracy and good precision.